Selective hyperpolarization of heteronuclear singlet states via pulsed microtesla SABRE - Tanner, Christian P. N. (J Chem Phys, 2019)
Signal Amplification By Reversible Exchange (SABRE) and its heteronuclear variant SABRE in SHield Enables Alignment Transfer to Heteronuclei create large nuclear magnetization in target ligands, exploiting level crossings in an iridium catalyst that transiently binds both the ligands and parahydrogen. This requires a specific, small magnetic field to match Zeeman splittings to scalar couplings. Here, we explore a different strategy, direct creation of heteronuclear singlet states in the target ligands, which produces enhanced signals at other field strengths, including zero field. We also show that pulsed methods (including pulsed field nulling) coherently and selectively pump such singlets, affording a significant enhancement on the resulting hyperpolarization.